Longitudinal Estimates of the Union Effects on Wages, Wage Dispersion and Pension Fringe Benefits - Swidinsky, R.; Kupferschmidt, M. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1991)
This study provides evidence of the union effect on wages, wage dispersion and pension fringe benefits derived entirely from the new Canadian longitudinal micro data base.